THE ROLE OF MADRASAH IBTIDAIYAH TEACHERS IN BUILDING STUDENTS' ISLAMIC CHARACTER THROUGH INTEGRATIVE THEMATIC LEARNING IN THE DIGITAL ERA - Gianistika , Chika; Tanjung, Rahman; Supriatna, Asep; Permana Suryadipraja, Rian; Saepudin, Saepudin (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The formation of Islamic character in the educational environment, especially in madrasas, is crucial for building students' moral and ethical foundations. Purpose: This research examines the role of Madrasah Ibtidaiyah teachers in fostering students' Islamic character through an integrative thematic learning approach adapted to technological developments in the digital era. Method: Using a qualitative case study at Madrasah Ibtidaiyah Tarbiyatul Athfal, data was collected through observation, interviews, and documentation, and analyzed descriptively. Result: The findings reveal that teachers who employ an integrative thematic approach effectively link lesson material to Islamic values, enabling students to understand and apply religious principles in daily life. Additionally, while the use of digital technology is still limited, teachers who manage digital tools well can enhance student motivation and engagement. The study also found that integrating technology with Islamic values helps students internalize Islamic character more deeply. Conclusion: The research underscores the importance of teacher training in utilizing technology as an effective learning tool, suggesting that madrasas should provide adequate support for teachers to integrate technology with Islamic character education. This approach aims to build a generation with noble morals in the digital era.